Comparative analysis of cystic biliary atresia and choledochal cysts - Chen, Yu-tong; Gao, Ming-juan; Zheng, Ze-bing; Huang, Lu; Du, Qing; Zhu, Dai-wei; Liu, Yuan-mei; Jin, Zhu (Frontiers in Pediatrics, 2022)
Objective: Cystic biliary atresia (CBA) is a rare and peculiar type of biliary atresia (BA) that is easily confused with infantile choledochal cysts (CCs). This study explored information for early CBA diagnosis and treatment. Method: The authors retrospectively analyzed the clinical data of 32 children with hilar cysts from January 2013 to May 2021. According to the diagnosis, they were divided into the CBA (n = 12) and CC (n = 20) groups. Patient features, biochemical indexes, preoperative ultrasound characteristics, cholangiography features, and intraoperative findings were analyzed and compared between the two groups. Results: The alanine aminotransferase, aspartate aminotransferase, total bilirubin, and direct bilirubin levels in the CBA group were higher than in the CCs group (P < 0.05). Additionally, B-mode ultrasound showed a cystic mass in front of the hepatic hilum, and the cyst size was much smaller in the CBA group compared with the CC group (2.2 ± 1.3 cm vs. 6.0 ± 2.2 cm, P < 0.001). Among all of the parameters, cyst width was the most accurate for identifying CBA and CCs. A cutoff value of 2.5 cm (area under the curve, 0.98, P < 0.001) showed 90.9% sensitivity and 95% specificity for cyst size. Conclusion: For children with early-onset severe jaundice, and if the width of the cystic mass was ≤2.5 cm, a diagnosis of CBA was highly likely. Early cholangiography and surgical treatment are necessary for the effective treatment of these infants.